Membran Polimer Elektrolit Nanokomposit Berbasis PVdF-HFP (Poly Vinylidene Flouride co-Hexaflouropropylene) sebagai Separator Baterai Lithium Ion dengan Variasi Non Solvent - Alviansyah Z.A. Putro; Nugroho F. Windyanto; Endah R. Dyartanti (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Rechargeable batteries consist of electrode, separator, and electrolyte. Separator used as medium transfer ions and to prevent electrical short circuits in battery cells. Commonly used a solid separator (polyethylene, celgard) and a liquid electrolytes. Recently poly(vinylidene fluoride) (PVdF) were developed into a based gel polymer electrolytes and as separator at once. The advantage of PVdF has a high porosity and more stable against hard chemical also high temperature. The aim of this research to investigate the effect of non-solvent to characteristic membranes. In order to produce better outcome add 7% polyvinylpyrrolidone (PVP) as a pore forming agent and 10% nonoclay as filler. Phase-inversion is a common methode to form a microporous membranes. This methode was prepared by dissolving Nanoclay and PVP in solvent for 2 hours, and then add the PVdF/PVdF-HFP with stirring at 60°C. After 4 hours, casting in a glass and immersed in non-solvent. N,N-Dimethylformamide (DMF) is used as solvent, while for non-solvent are variated: aquadest, N-Methyl Pyrollidone (NMP) 10%, Natrium Clorida (NaCl) 10%. The membranes were characterized by porosity test, electrolytes uptake test, and Fourier Transform Infrared (FTIR). The best result using aquadest as non-solvent provide 60% electrolyte uptake, and with non-solvent NaCl give porosity 80%